"All I can See of My Country": Representations of Precarity in Selected Poems of Mxolisi Nyezwa. Issue 2 (2nd July 2020) - Allan, Kyle
Abstract : With poems that convey concisely the existential state of living in precarity, Mxolisi Nyezwa offers a unique and crucial voice in South African literature. This article discusses representations of precarity and related concepts of "slow death" (Berlant 2007), "slow violence" (Nixon 2011), and "cruel optimism" (Berlant 2011), focusing on several selected poems from Nyezwa's (2011) volume Malikhanye . The article engages with his ability to react to precarity via the revitalisation of language and the effective mobilisation of innovative aesthetic strategies. Nyezwa's poems foreground the precarity that has been experienced through socio-politico-economic factors, including the often neglected factor of environmental degradation; they also emphasise the process(es) of grieving and the concept of grievability, and encourage an embrace of human vulnerability, while simultaneously connecting personal loss to the greater context of societal precarity. His work reveals that a revitalisation of poetic language can react to and challenge precarity.